Fauna, flora i cudowność — zagadki Wojciecha Tylkowskiego - Deskur, Aleksandra (Motywy fauny i flory w literaturze i kulturze, 2018)
The aim of this paper is to analiyze the motives connected with a natural science in scientific treatise written by Wojciech Tylkowski — The Wise Conversations. Wildlife, animals and plants are important components of Tylkowski’s work — and a scientific interest in the evironment let researchers recognize The Wise Conversations as an example of very atractive type of Baroque literary production, called scientia curiosa (“interesting science”). In general this kind of literature is known of science popularization, making common knowledgle more fascinating and encouraging people to pay some attention to scientific questions.